Forest areas in the southern central Rif between multiple economic roles and prospects for sustainable management: Taounate constituency as a model - Hini, Mohammed; El-Bazoui, Jaouad; Errafik, Mohammed (Journal of natural sciences, life and applied sciences, 2025)
The southern central Rif has a diverse and dense forest heritage (conifers, cedars, oaks, etc.). This was formed and sustained by a set of natural, historical and organizational conditions. The fragile economic and social conditions of the local population have contributed to their heavy reliance on the forest. Such conditions have led them to play multiple roles in terms of energy, fodder and pastoral... The increasing pressure on the forest in the light of the structural transformations that the area has witnessed, particularly those related to the natural conditions characterized by climatic heterogeneity and the territorial expansion of cannabis cultivation, has led to a decline in the forest area annually by an average of 100 hectares.  To save the forest and ensure its sustainability, the authorities in charge for the sector have made great efforts to protect and maintain forest products through technical interventions and legal procedures, to restore equilibrium to the forest eco-system in the southern central Rif. This study aims to highlight the various economic forest roles and the measures state-taken to protect it from deterioration. The paper relied on the descriptive analytical approach and a field questionnaire covering 350 families. The most important results obtained can be summarized here: The multiple economic functions of the forest (it contributes 81.2% of the firewood consumed in the region, about 39.68% of the fodder units, and approximately 1,737,925 dirhams annually in financial resources for territorial communities). Concerning the state's interventions to protect the forest, they consisted of reforesting 1,101 hectares and administratively defining 78.7% of the forest property.
Keywords: southern central Rif; forest; forest protection; sustainability; reforestation